Identifikasi Faktor-Faktor yang Mempengaruhi Kemampuan Pemecahan Masalah Matematika - Ni Komang Vonie Dwianjani; I Made Candiasa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
This research aimed for 1) analyzing the factors which contributed the ability to solve mathematical problems and (2) identifying the domination of the aforementioned factors. This research was conducted to grade 8 in all state junior high schools in the city of Singaraja, academic year of 2017/2018 with 377 participating students which were taken with stratified cluster random sampling technique. This research method was an quantitative ex-post facto research. The data of this research were taken using story math problem about SPLDV, Pythagoras, Lingkaran and were analyzed with factor analysis. The research has found that the factors which contributed the ability to solve mathematical problem are identify problem (identify), define goal (define), explore possible strategies (explore), act on strategies (act) and look back (look). These five factors could be categorized into two components, namely: analytical ability component which consists of identify problem and define goal , and systematical ability component which consists of explore possible strategies, act on strategies and look back. Furthermore, it was also found that the factors which dominated the ability to solve mathematical problem was executing the act on strategies and followed by explore possible strategies, identify problem, define goal, and look back.